Call Names in Unofficial Communication of the Military: Specificity of Creation and Lexico-Semantic Base - Shulska, Nataliia; Kostusiak, Nataliia; Rymar, Nataliia; Zavarynska, Iryna; Mykhalchuk, Svitlana; Bovda, Olena (My University, 2022)
The article identifies and analyzes call names in the unofficial communication of the military, evidenced in journalistic texts from the beginning of the full-scale invasion of Russia (based on the material of such media as “Gazeta po- ukrainskyi”, “Konkurent”, “Suspilne Novosti”, “VolynPost”, “Apostrophe TV”, “Pyatiy.yua”, etc.). The functional nature, combat history, motivational status, lexical- semantic base and peculiarities of creation, connotative coloring of the “second” names of Ukrainian fighters were studied. It has been observed that military pseudonyms actively function in journalistic materials, as evidenced by their large number in texts on military topics, as well as their appearance in headlines and leads. Unofficial anthroponymic factage is differentiated into ten lexical-semantic groups by the keyword-motivator: names by external or internal features of denotations; nominations by occupation, profession or hobby of a person; floronoments; faunonomena; naming other persons (movie and multi-heroes, fairy-tale characters, biblical or mythical creatures, actors, athletes, politicians, writers, etc.); ethnonyms or names of other nationalities, countries; lexemes denoting family relations; Ukrainian or foreign names (own or foreign). Usually, the colloquial version of one's personal name is reflected at the base of the call sign, consonant name as an association to the official surname, names of appliances and household appliances, nominations of phenomena of nature, space, landscape. Some call signs of the Ukrainian military are not included in any motivational group, because these names are single or creative lexemes with multiple meanings. In media materials, such terms as military pseudonyms are used mainly, such as call sign, call name, combat nickname, military nickname, less often – pseudo and nickname. Journalists have repeatedly researched the nicknames of Ukrainian fighters themselves, devoting entire publications to them. The most diverse cases of the appearance of “second” names in the military have been revealed: they are invented by the soldiers themselves, they are given by comrades in the service, given by the military leadership; this is facilitated by a combat history or some unusual incident. Military call signs usually meet a number of criteria: there cannot be the same names; the word that identifies the person should sound clear, be short, and have masking properties. The motivational nature of unofficial designations in the mass media is presented mainly in the quotes of the military themselves, where they explain the origin of their name, or in the testimony of their combat comrades. The nominative base of the unofficial military noun is made up of anthroponyms with unknown motivation, as well as those whose creative lexemes do not cause direct associations in the minds of Ukrainian speakers. It is noted that the fixation and research of this anthroponymic category is important not only for its linguistic and communicative features, but also because today it is very important to preserve these names in popular memory through scientific studies, since over time they may be lost and fall out of use.
Keywords: Nickname; Military; Unofficial communication; Mass media; Russian- Ukrainian war; Motivational group; Lexical-semantic base